Iron Oxide Nanoparticles Derived from Mill Scale Waste as Potential Scavenging Agent in Dye Wastewater Treatment for Batik Industry - Azdiya Suhada, Abdul Rahim Arifin; Ismayadi, Ismail; Abdul Halim, Abdullah; Farah Nabilah, Shafiee; Rodziah, Nazlan; Ibrahim, Idza Riati (Scientific.Net, 2017)
In this work, iron oxide were derived from millscale has been used as a potential scavenging agent in wastewater treatment due to its high adsorption capacity and its shorter sedimentation time during wastewater treatment. Iron oxide obtained from the magnetic separation technique was subjected to high energy ball milling (HEBM) at different milling time to produce different size of nanoparticles of iron oxide. X-ray diffraction (XRD), Field Emission Scanning Electron Microscope (FESEM) and Scanning Trasmission Electron microscopy (STEM) were performed to study the morphological properties of the iron oxide nanoparticles. After HEBM, iron oxide nanoparticles were modified with Hexadecyltrimethylammonium Bromide (CTAB) to study the adsorption possibility of iron oxide nanoparticle modified with CTAB (Iron oxide– CTAB nanoparticles) in dye wastewater. The variation effect of particle size of derived Iron oxide– CTAB were studied. Permanent magnet was used to separate iron oxide nanoparticles from the solution. The clear part of the solution (treated wastewater) was filtered out and adsorption efficiency of Iron oxide– CTAB nanoparticles was measured using UV – Visible spectroscopy. Efficiency adsorption of iron oxide nanoparticles modified with CTAB greatly achieved above 99 % and the size of iron oxide nanoparticles was found to be affecting its performance in dye wastewater treatment